Deliberative democracy in practice - Kahane, David J. (David Joshua), 1962- (UBC Press, 2010)
Deliberative democracy is a dominant paradigm in normative political philosophy. Deliberative democrats want politics to be more than a clash of contending interests, and believe that political decisions should emerge from reasoned dialogue among citizens. But can these ideals be realized in complex and unjust societies? Deliberative Democracy in Practice brings together leading scholars who explore debates in deliberative democratic theory in four areas of practice: education, constitutions and state boundaries, indigenous-settler relations, and citizen participation and public consultation. They address issues such as whether the desire to rear deliberative citizens can be reconciled with the freedom of parents to raise their children in their own belief systems, and whether real-world designs for citizen participation and consultation live up to the norms of deliberative democracy. This dynamic volume casts new light on the strengths and limitations of deliberative democratic theory, offering guidance to policy makers and to students and scholars interested in democratic justice.